(untitled) (Journal of Atomic and Molecular Sciences, 2022)
Three derivatives based on oligothiophenes were theoretically investigated about the electronic and charge transport properties using density functional (DFT) theory based on the Marcus-Hush theory. The predicted highest hole mobility is 0.218 cm^2V^-1s^-1, and the highest electron mobility is 0.373 at 300 K. The calculated data demonstrated that the compound 1 should be a high-performance n-type organic material candidate and compound 3 may well be potential p-type materials with high mobility values. Our work also indicates that the face-to-face π-π interaction and S-S interactions is favorable for the molecular stacking and charge transport behaviors. The calculated results provide an additional possibility to be able to improve the origin semiconductor performance and design new electronic devices.